دراسة إحصائية لبعض العوامل المسببة لنقص وزن الولادة - حمود, زبيدة خضر (Latakia University Journal -Medical Sciences Series, 2019)
الهدف من البحث هو تحري بعض عوامل الخطورة لنقص وزن الولادة ومدى ارتباطها بولادة طفل ناقص وزن الولادة. أجرى هذا البحث في مشفى الأسد الجامعي باللاذقية قسم التوليد وأمراض النساء بين العامين (2009 – 2010) ضمت الدراسة (150) وليد تم اختيارهم عشوائيا، وتم تحري بعض عوامل الخطورة باستجواب والدتهم ومن ثم تم دراسة مدى ترابط هذه العوامل مع نقص وزن الولادة. ضمت العوامل المدروسة: عمر الأم، مستوى الثقافة، وزن الأم قبل الحمل، عدد الأجنة، عدد الولادات، أمراض الأم (ارتفاع الضغط الشرياتي، فقر الدم ). توصلنا إلى أن نسبة LBW كانت عالية بين الولدان لأمهات لديهن واحد أو أكثر من العوامل التالية: عمر الأم ‹25 سنة (50%)، وذوات الثقافة المتدنية (‹6 سنوات من التعليم ) (27.5%) وزنهن قبل الحمل (‹45 كغ ) (50%) الحمل التوأمي (30%)، الولودات (أكثر من ولادة واحدة )(25%)،ارتفاع توتر شرياني (23.33%) ، فقر دم (22.80%) مقارنة مع الولدان لأمهات لديهن واحد أو أكثر من العوامل التالية : عمر الأم (26-30) سنة (10.9%) ذوات الثقافة الجيدة (›12سنة من التعليم) (11.4%)، وزنهن قبل الحمل(≥56كغ) (10%)، الحمل المفرد (15%) الخروسات (10%)، ليس لديهن ارتفاع توتر شرياني (19.16%)، ليس لديهن فقر دم (18.27%). This research tends to investigate the extent of the effect of the risk factors of the newborns underweight. However, it is conducted at Tishreen University Al-Assad Hospital OB / Department of Gynecology, in the period 2009-2010. It included 150 infants randomly chosen. Some risk factors have been detected by questioning their mothers. Then, the extent of the interrelation between those factors and the newborns' underweight has been the focus of our study. The studied factors included: mother’s age, her level of education, her weight antenatal, number of embryos, number of deliveries, her diseases (Arterial Hypertension, Anemia). We have concluded that the rate of LBW was high among the infants born from mothers having one or more of the following factors : Mother’s age /25/ years (50%), of poor education (6 years of learning), (27.5%), the weight of the mothers antenatal 45 kgs, (50%), twin pregnancy (30%), multiple birth (25%), arterial hypertension (23.33%), anemia (22.80%). Comparison with the infants born from mothers who have one or more of the following factors: mother’s age /26-30/ years (10.9%), of good education (12 years of learning), (11.14%), the weight of the mother's antenatal 56≤ kgs, (10 %), mono- pregnancy (15%), prime gravida (10%), free from arterial hypertension (19.16%), free from anemia (18.27%).